The Gade Clean And Gold: Increasing Financial Inclusion Of Gold Savings Products For Sustainable Green Economy - Ning Karnawijaya; Lila Pangestu Hadiningrum; Siti Rokhaniyah (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2021)
The gade clean and gold program applies the triple bottom line principle by prioritizing balance and harmony in the economic, environmental, and social aspects, namely “separating waste and saving gold”. Through the gade clean and gold program, PT. Pegadaian seeks to carry out sustainable community development activities to reduce poverty and social injustice, improve environmental conditions, and assist the government in waste management. The gade clean and gold corporate social responsibility (CSR) program seek to build public awareness to save the environment from pollution, especially waste, and the global save the earth program. The purpose of this study is to describe how CSR as a social program can increase the financial inclusion of gold savings and realize a sustainable green economy. This study uses the paradigm used is constructivism and a mixed-method approach. The results of this study indicate that gade clean and gold can realize a sustainable green economy. On the pillar of commitment to the environment, this activity has helped reduce visible environmental problems, namely the waste problem. The social pillar shows that this program can mobilize the community to increase their social capacity. On the economic pillar, this program can increase financial inclusion, especially in gold savings-investment products.